Current trends and future potential in the detection of avian coronaviruses: An emphasis on sensors-based technologies - Md Safiul Alam Bhuiyan; Suman Das Gupta; Juplikely James Silip; Saranika Talukder; Md Hakimul Haque; Jade K. Forwood; Subir Sarker (Elsevier, 2025)
Infectious bronchitis virus (IBV), an avian coronavirus, member of the genus Gammacoronavirus, poses significant threats to poultry health, causing severe respiratory, reproductive, and renal infections. The genetic diversity of IBV, driven by mutations, recombination and deletions, has led to the emergence of numerous serotypes and genotypes, complicating both diagnosis and control measures. Rapid and accurate diagnostic tools are essential for effective disease management and minimizing economic losses. Conventional diagnostic methods, such as PCR, virus isolation, and serological assays, are hindered by limitations in sensitivity, specificity, and turnaround time. In contrast, innovative biosensor platforms employing advanced detection mechanisms-including electrochemical, optical, and piezoelectric sensors-offer a transformative solution. These technologies provide portable, highly sensitive, and rapid diagnostic platforms for IBV detection. Beyond addressing the challenges of conventional methods, these biosensor-based approaches facilitate real-time monitoring and enhance disease surveillance. This review highlights the transformative potential of biosensors and their integration into diagnostic strategies for avian coronavirus infections, presenting them as a promising alternative for precise and efficient IBV detection.